Effect of Long Chain n-3 PUFA on Endothelial Activation, Endothelial Function and Atheromatous Plaque Stability - Roos, Baukje d.; Mercer, Derry K.; Wainwright, Cherry; Thies, Frank (Current Nutrition & Food Science, 2005)
Several studies have provided support for the protective effects of long chain n-3 polyunsaturated fatty acids (n-3 PUFA) against cardiovascular disease (CVD). N-3 PUFA may decrease the risk of CVD by improving plaque stability and endothelial activation and/or function. Compared with the considerable amount of literature describing the effects of n-3 PUFA on CVD, relatively little consistent information is available about the mechanism by which this occurs. The aim of this review is to overview the literature that provides insight into our current understanding of the mechanisms by which PUFA improve endothelial function and assist in plaque stabilization in atherosclerosis.
Keywords: inflammation